METODE PENDIDIKAN MENURUT PETUNJUK AL-SUNNAH - Lubab, Nafiul (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2014)
AbstractEducation is very vital role in human life. The system of education in whicheducational methods is under constant continuous "immortal-conversation",especially in methods of Islamic education, the epistemology of al-Quran and alSunnah. Science always continues to grow, so did the methods of education inthe interpretation of the al-Quran and al-Sunnah. As the principal basis of bothal-Sunnah provides practical translation of articulation over-methodical practicedaily with the companions of the prophet in education. Nevertheless, there is aproblem regarding Muslims repetition educational method that in fact ittawadlu relationship between educators and students, education is rare that thesubject and object in the students.Experts Islamic figures revealed some nuances of Islamic educational methodson the main source of epistemology. Such as Abu Ali Husain ibn Abd Allah ibnHasan ibn Ali ibn Sina (980-1037 AD) method of reward and punishment, AbuMuhammad al-Ghazali (1058-1111 AD) method of gradual habituation, Abdurrahman Abu Zaid ibn Khaldun (1322-1406 AD) phasing method of repetition (tadarruj wa al-tikrar), Abdul Fattah Abu Ghuddah (2009) titled 40 Methods Education & Teaching Prophet, then an-Nahlawi Abdurrahman (1995), Islamic education: at home, school, and community, by dividing 7 methods ofeducation, M.Thalib (1996), Islamic educational methods 30T, he divided into30 educational methods that begin with the letter T and many other alternativemethods.The author analyzes existing educational criticized by giving an inductivedeductive method, an educational method that makes the active, creative, how to make the education of students as actors. Educators here in the position of adult foster children in ushering in meeting the educational goals that address the challenges of life in her future students.Keywoard: metode pendidikan, al-Sunnah